2016
DOI: 10.1080/10942912.2015.1107734
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Determination of the Antifungal Activity of Artemisia campestris Essential Oil from Algeria

Abstract: The chemical composition of the essential oil isolated from the aerial parts of Artemisia campestris from Algeria and its antifungal activity against 10 filamentous fungal strains were investigated. The A. campestris essential oil was obtained in a yield of 0.71% (v/w). The major constituents of the oil were α-pinene (18.65%), β-pinene (16.78%), β-myrcene (17.34%), and germacrene D (10.34%). Our study showed that A. campestris essential oil was a potent antifungal agent against some pathogenic fungal species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…The EO was better than the ME since its application by the above different methods resulted in stronger inhibition of the mycelial growth besides the total inhibition of spore germination by disc diffusion method and its fungicidal effect at 2.5 µL/mL by well-dilution test. This latest result is clearly in concordance with that mentioned by Houicher et al (2016) about P. expansum and other pathogenic and toxicogenic fungi. Secondary metabolites of plants have been tested for their antimicrobial activity and a significant number of plant extracts and essential oils have been showen to possess antimicrobial activity (Rahman et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The EO was better than the ME since its application by the above different methods resulted in stronger inhibition of the mycelial growth besides the total inhibition of spore germination by disc diffusion method and its fungicidal effect at 2.5 µL/mL by well-dilution test. This latest result is clearly in concordance with that mentioned by Houicher et al (2016) about P. expansum and other pathogenic and toxicogenic fungi. Secondary metabolites of plants have been tested for their antimicrobial activity and a significant number of plant extracts and essential oils have been showen to possess antimicrobial activity (Rahman et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…SOD, CAT, and GPx activities, as antioxidant enzymes, play an important role in the protection against the deleterious effects of LPO by scavenging superoxide anions and hydroxyl ions. ACEO was also reported to combat effects of many toxins, including pesticides and heavy metals ( Badraoui et al, 2012 ; Houicher et al, 2016 ; Saoudi et al, 2017a ). In our experiment, pre-administration of ACEO or vitamin C against CPF resulted in an increase in the activities of SOD, catalase and GPx in the liver and kidney tissues of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Another work revealed the existence of the major volatiles spathulenol and β -pinene in essential oil of A. campestris L. from Serbia [ 2 ]. Previous studies reported the existence of two chemotypes of A. campestris L. essential oil occurring in different localities; the most relevant chemotype consists mainly in β -pinene alone or together with α -pinene occurring mainly in Tunisia [ 14 , 59 – 62 ], Algeria [ 10 , 63 – 65 ], and Southern Ural [ 66 ], while the other chemotype was characterized by the volatiles: tremetone and capillen, detected in essential oil of A. campestris L. growing in Turkey [ 24 ]. Moreover, it is known that the species A.campestris L. presents great variability in its essential oil composition due to the existence of different subspecies from different localities.…”
Section: Discussionmentioning
confidence: 99%